Calibrated Electrochemical Impedance Spectroscopy and Time‐Domain Measurements of a 7 kWh Automotive Lithium‐Ion Battery Module with 396 Cylindrical Cells. Issue 2 (3rd January 2023) - Kasper, Manuel; Moertelmaier, Manuel; Ragulskis, Mykolas; Al‐Zubaidi R‐Smith, Nawfal; Angerer, Johannes; Aufreiter, Mathias; Romero, Alberto; Krummacher, Jakob; Xu, Jianjun; Root, David E.; Kienberger, Ferry
Abstract: A 7 kWh automotive battery module with 396 interconnected cells was tested with electrochemical impedance spectroscopy (EIS) and time‐domain pulsing over 260 charge‐discharge cycles. An EIS calibration workflow was developed for low complex impedance values in a frequency range of 1 kHz to 50 mHz. Significant corrections on the resistance and the reactance were obtained from the calibration, particularly at frequencies above 100 Hz. Equivalent circuit parameters were extracted from the EIS spectra and the pulse response and investigated with respect to the cycle number and state‐of‐charge (SoC). Fit parameters were robustly extracted including R sol, R ct, and L from EIS, and R 0, τ 1 and τ 2 from time‐domain pulsing. The ohmic resistance decreased over the cycling number indicating an enhanced wetting of the electrodes. Charge transfer resistance R ct showed a monotonic increase over the cycles related to cell ageing. From the charge and discharge pulses, the ohmic resistance R 0 was determined from the instantaneous voltage step of the recovery pulse, while the two time constants τ 1 and τ 2 correspond to the slower exponential recovery phase. R 0 from the time‐domain showed a similar trend as R sol plus a contribution of R ct from EIS. Overall, we show that calibrated EIS and time‐domain pulsing are efficient methods to gain insights into the electrochemical processes related to different SoCs and the cycling ageing of battery modules and packs. Abstract : A module test system : A 7 kWh automotive lithium‐ion battery module with 396 cylindrical cells is characterized using calibrated electrochemical impedance spectroscopy (EIS) and time domain measurements. Based on EIS and time domain pulsing, robust model parameters are extracted, providing insights into the electrochemical processes of battery modules at different SoCs as well as cycling ageing.